Halal Tourism Marketing in the Disruption Era: A Case Study of Penyengat Island in Riau Islands Province: Pemasaran Pariwisata Halal pada Era Disrupsi: Studi Kasus Pulau Penyengat di Provinsi Kepulauan Riau - Destiana, Riska; Kismartini, Kismartini (Society, 2020)
The disruption era creates great opportunities for halal tourism development by using technology to market halal tourism products. As a pilot project for the halal tourism development, Penyengat Island in Riau Island Province faces the challenges in building its image as a leading halal tourism destination. This study aims to analyze the halal tourism marketing, in this case, digital marketing, on Penyengat Island in the disruption era. This research used descriptive qualitative methods through a literature study with data sources derived from related journal articles and other literature. The efforts of halal tourism marketing for Penyengat Island are not implemented digitally. To market tourism of Penyengat Island, the local government and stakeholders use mass media advertising, billboards, annual festivals, and digital channels such as social media, online booking sites, and e-book guides at halaltrip.com. Yet, the media does not inform tourism events or indicate Penyengat Island as a halal tourism destination. It proves that inadequate information about the concept of halal tourism and/or other available information on halal tourism travel guides for Muslim tourists on the digital platforms used. The efforts to promote Penyengat Island as halal tourism using digital channels are the relevant interesting contents in digital marketing channels, the availability of information on the need for halal services, and innovation on tourism attractions.